Altitude’s Impact on the Rhizosphere Prokaryotic Communities of the Cretan Endemic Plant Petromarula pinnata (L.) A.DC. - Rafaela Stagiopoulou; Ifigeneia Mellidou; Nikos Krigas; Effimia M. Papatheodorou (Microorganisms)
The present study examined the effect of the three different altitudes on the enzymatic activity and the prokaryotic communities of the rhizosphere of Petromarula pinnata (L.) A.DC. (Campanulaceae), a vulnerable local endemic species of Crete (Greece). It was observed that the pH and N-acetylglucosaminidase (NAG) activity increased with altitude while the β-1,4-glucosidase (BG) activity fluctuated with increasing altitude. The prokaryotic community in the rhizosphere of P. pinnata was dominated at the phylum level by Proteobacteria, Actinobacteriota, Bacteroidota, and Firmicutes, as well as by Bacillus members at the genus level. The alpha diversity did not vary with altitude while the b-diversity varied significantly, reflecting differences in community composition in relation to altitudinal gradient. The NAG activity was positively associated with most of the predominant phyla, except for Proteobacteria. The BG enzyme activity appeared to be negatively associated with Proteobacteria, Chloroflexi, and Acidobacteriota. Based on online databases, the predicted functions of the community showed a clear distinction in relation to altitude. At lower altitude, functions related to quorum sensing among microbes were overrepresented, while at the higher altitude, the functions were more related to energy production and transfer. The results of this research contribute to the ex situ and in situ protection of the vulnerable populations of P. pinnata and provide information for understanding the effect of altitude on processes in the rhizosphere of a threatened local endemic species of Crete studied in its original habitats.